EFFICACY OF AS-NEEDED INTRAVITREAL INJECTION COMPARED TO 3-MONTHLY LOADING OF ANTI-VASCULAR ENDOTHELIAL GROWTH FACTOR AGENTS FOR BRANCH RETINAL VEIN OCCLUSION - KHAN , TA; NAVEED , S; RIAZ , S; ANJUM , S; NAUREEN , F; HASSAN , A (Biological and Clinical Sciences Research Journal, 2024)
Branch retinal vein occlusion (BRVO) is a prevalent retinal vascular disorder and a significant cause of vision impairment, particularly in individuals over the age of 50. Objective: The basic aim of the study is to find the efficacy of as-needed intravitreal injection compared to 3-monthly loading of anti-vascular endothelial growth factor agents for branch retinal vein occlusion. Methods: This prospective, comparative study was conducted at Al-Shifa Trust Eye Hospital, Rawalpindi from January 2024 to August 2024. A total of 55 patients diagnosed with BRVO were enrolled in the study. Results: Data were collected from 55 patients with a similar mean age of 53.45 ± 4.56 years and 52.4 ± 7.01 years, respectively. At baseline, the mean best-corrected visual acuity (BCVA) was comparable between the two groups (55.2 in Group A vs. 54.7 in Group B, p = 0.67), as was the mean central retinal thickness (CRT) (485.6 µm in Group A vs. 490.3 µm in Group B, p = 0.73). There were no statistically significant differences between the groups in these baseline characteristics. Conclusion: It is concluded that both the PRN-only and loading phase + PRN regimens are effective for treating BRVO, with the loading phase regimen providing slightly superior visual outcomes.